The Environmentally IPM Package for Controlling Fall Armyworm (Spodoptera frugiperda) in Maize Field - Nova Yurina; My Syahrawati; Arneti Arneti; Munzir Busniah (Jurnal Proteksi Tanaman, 2023)
Integrated Pest Management (IPM) is a pest control method that combines several control techniques by considering ecological, economic, and sociological consequences. Management efforts with IPM principles can be conducted by cultivating healthy plants and entomopathogen application. This study examined the IPM package's success for controlling fall armyworm (Spodoptera frugiperda) in maize field. This research was conducted in a farmer's maize plantation in the West Pasaman District from August to December 2021. The study used a Randomized Block Design (RBD) which consisted of three treatments and five replications. The treatments were different cultivation techniques using IPM, Non-IPM, and control. The variables observed were the population of S. frugiperda (individual/plant), attack rate (%), attack intensity (%), cob weight (g/cob), and farming cost (IDR). The results showed that the IPM and Non-IPM maize cultivation techniques had no different effect on S. frugiperda, especially survival stage, attack rate, intensity, and yield. However, this effect was higher than the control. In addition, the economic benefits of cultivation with IPM were higher than non-IPM. Therefore, this IPM package can be recommended for controlling S. frugiperda because it is also economically profitable and environmentally friendly.